2011
DOI: 10.1111/j.1742-4658.2011.08213.x
|View full text |Cite
|
Sign up to set email alerts
|

Novel suppression mechanism operating in early phase of adipogenesis by positive feedback loop for enhancement of cyclooxygenase‐2 expression through prostaglandin F receptor mediated activation of MEK/ERK‐CREB cascade

Abstract: Prostaglandin (PG) F 2a suppresses adipocyte differentiation by inhibiting the function of peroxisome proliferator-activated receptor c. In this study, we identified a novel suppression mechanism, operating in the early phase of adipogenesis, that increased the production of anti-adipogenic PGF 2a and PGE 2 by enhancing cyclooxygenase (COX) 2 expression through the PGF 2a -activated FP receptor ⁄ extracellular-signal-regulated kinase (ERK) ⁄ cyclic AMP response element binding protein (CREB) cascade. COX-2 exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
1
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 47 publications
1
43
1
1
Order By: Relevance
“…These data differ from results published previously in which it was shown that FP receptor expression increases with 3T3-L1 adipogenesis (46) and that FP receptor stimulation by fluprostenol decreases FP receptor expression in preadipocytes (52). These differences may be due to clonal differences in the 3T3-L1 cells used and the fact that activation of FP by different agonists might produce different effects.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…These data differ from results published previously in which it was shown that FP receptor expression increases with 3T3-L1 adipogenesis (46) and that FP receptor stimulation by fluprostenol decreases FP receptor expression in preadipocytes (52). These differences may be due to clonal differences in the 3T3-L1 cells used and the fact that activation of FP by different agonists might produce different effects.…”
Section: Discussioncontrasting
confidence: 57%
“…Bimatoprost, PGF 2␣ EA, and PGF 2␣ all induced a large increase in Ptgs2 expression in 3T3-L1 cells treated with IDM adipogenic medium, as has been observed also with the FP receptor agonist fluprostenol in undifferentiated 3T3-L1 cells, resulting in increased de novo PGF 2␣ production (52). The fluprostenol-mediated induction, however, was transient, being observed for only 1 h, after which Ptgs2 transcript levels decreased significantly below base line.…”
Section: Discussionmentioning
confidence: 88%
“…MAPK1 also reportedly regulates adipogenesis [29,30]; however, its roles in this process are complicated. On the one hand, MAPK1 up-regulates the expression of crucial adipogenic regulators such as peroxisome proliferator-activated receptor c (PPARc) and the CCAAT-enhancer-binding proteins a, b, and d at the beginning of adipogenesis [31,32].…”
Section: Introductionmentioning
confidence: 98%
“…Knockdown of aldo-keto reductase 1B3 (AKR1B3), a PGFS, decreased de novo PGF 2 ␣ biosynthesis in 3T3-L1 cells and then further promoted lipid accumulation ( 13 ). It has been shown that PGF 2 ␣ suppressed adipogensis by enhancing phosphorylation of PPAR ␥ via prostaglandin F receptor-activated MEK⁄ERK cascade ( 14 ). On the other hand, PGE 2 , a precursor of 15-keto-PGE 2 , is the most abundant prostaglandin produced in 3T3-L1 preadipocytes, and the highest level of PGE 2 was detected during the early phase of adipogenesis ( 15,16 ).…”
Section: Ptgr-3 Decreases Proadipogenic Effect Of 15-keto-pge 2 Throumentioning
confidence: 99%